Incentives for process innovation in a collusive duopoly - Christoph Engel (Max Planck Institute for Research on Collective Goods, 2007)
Two suppliers of a homogenous good know that, in the second period, they will be able to collude. Gains from collusion are split according to the Nash bargaining solution. In the first period, either of them is able to invest into process innovation. Innovation changes the status quo pay-off, and thereby affects the distribution of the gains from collusion. The resulting innovation incentive is strictly smaller than in the competitive case.
Keywords: D43; K21; L13; O31; 330; Duopoly; Collusion; Innovation Incentives; Innovation; Ökonomischer Anreiz; Innovationswettbewerb; Wettbewerbsbeschränkung; Immaterialgüterrechte; Theorie